Conceptual Framework for Fintech in Sharia Financial Planning - Masmuh, MuhammadMuktiArif; Rahmawati; Fahmi, Muhammad; Khan, Faisal Iqbal Ahmad (Li Falah: Journal of Islamic Economics and Business, 2024)
The integration of financial technology (fintech) with Islamic financial planning presents both opportunities and challenges in the rapidly evolving financial landscape. This study aims to develop a conceptual framework for implementing fintech solutions in Islamic financial planning while ensuring Shariah compliance. Through a comprehensive literature review, we identify five core processes essential for successful integration: identification of target groups and Shariah- compliant practices, customer awareness and engagement, standardization of Shariah-compliant operations, technological innovation implementation, and continuous evaluation and improvement. The research reveals that while Indonesia's large Muslim population presents significant growth potential for Islamic fintech, several challenges persist, including limited regulatory frameworks, inadequate human resources, and the need for standardized Shariah compliance measures. The study contributes to the existing literature by proposing a structured framework that can guide financial institutions, regulators, and fintech developers in creating effective, Sharia-compliant financial planning solutions. This framework addresses the growing need for accessible Islamic financial services while maintaining religious principles in an increasingly digital financial ecosystem.